The Little Dipper of the Flint Hills - Danny Caine (Symphony in the Flint Hills, 2018)
Introduction: The kitchen staff of Strong City’s Ad Astra Food and Drink amicably lounge at tables during a power outage. They have all heard of the artesian well nearby but cannot give precise directions to it. Someone suggests that it’s near Wonsevu, a tiny hamlet in southeast Kansas’s Chase County nestled in the heart of the Flint Hills. (Originally published in Ebb and Flow: Water/Ways Stories from Kansas, Kansas Humanities Council.)